TEI in LMNL: Implications for Modeling - Wendell Piez (Journal of the Text Encoding Initiative)
LMNL (the Layered Markup and Annotation Language) is a small, if ambitious, research project in text encoding. Unlike XML, LMNL markup does not represent document components or constituents (as “elements”) within a structure, but rather simply labels ranges of text within the document for identification and processing. Avoiding choices between structures, any and all structures can be elucidated; this reveals not only new capabilities for the digital processing of humanities texts—simultaneously building on TEI and extending it to new uses—but also something about the way our tools condition our view of our objects of study. This paper presents LMNL and suggests some of its strengths in the context of TEI.